Korelasi Pengetahuan Kesehatan Reproduksi Terhadap Pola Pacaran Remaja Pada Kelas XII SMA Di Samarinda - Yasmine Putri Fadhilah; Hudi Winarso; Sarah Hagia Lestari (Bahasa Indonesia, 2023)
Knowledge of reproductive health is important, given the existence of premarital sex in Indonesia, especially in East Kalimantan. Dating behaviours can be influenced by internal and external factors. One of the external factors is education. This study aims to determine the relationship between adolescent reproductive health knowledge and dating behaviours. This research method is a descriptive-analytic survey with a quantitative research type with a cross-sectional approach. The sampling technique was proportionate stratified random sampling so that the number of respondents was 200 people and the research instrument used was a questionnaire. The results showed that the majority of respondents had adequate (43.5%) to good reproductive health knowledge (53.5%), the dominating dating behaviour is risky dating behaviour, with the majority of respondents wanting to hold hands (4.3%), hugging (4.3%), kissing (4.2%) and premarital sex (4%), while those who have done holding hands (4.2%), hugging (4.2%), kissing (4.2%) and premarital sex (4.3%). The results showed a relationship between reproductive health knowledge and dating behaviour. Keywords: Teenagers, Health reproduction knowledge, Dating behaviours